Person Job Fit, Job Embeddedness dan Self Efficacy Terhadap Organizational Citizenship Behavior dengan mediasi Organizational Commitment - Zahra, Laela May Az; Suciningtyas, Santi; Masrokhah, Siti; Ningsih, Diah Wuriah (EconBank: Journal of Economics and Banking, 2024)
This study aims to analyze the influence of Person Job Fit, Job Embeddedness, and Self Efficacy on Organizational Citizenship Behavior with Organizational Commitment as a mediating variable among employees of the Social Affairs Office of Population Control, Family Planning, Women, and Children of Pemalang Regency. The sample collection used a census method with 66 respondents. The results of the multiple linear regression analysis showed a positive effect of Person Job Fit on Organizational Citizenship Behavior, a positive effect of Job Embeddedness on Organizational Citizenship Behavior, a positive effect of Self Efficacy on Organizational Citizenship Behavior, and a positive effect of Organizational Commitment on Organizational Citizenship Behavior. The t-test results indicated that Person Job Fit, Job Embeddedness, and Self-Efficacy have a significant influence on Organizational Citizenship Behavior. Additionally, the Sobel test results showed that Person Job Fit, Job Embeddedness, and Self Efficacy significantly influence Organizational Citizenship Behavior through Organizational Commitment.